Knowledge regarding sexual and reproductive health among adolescents in higher secondary school - Shrestha, Kopila; Awale, Shanti (Journal of Chitwan Medical College, 2017)
Background: Adolescent reproductive health is one of the component of the reproductive health. It is most important issue in the world. Reproductive capability is taking place at an earlier age and adolescents are indulging in risk taking behaviors day by day. The objective of this study is to assess knowledge regarding sexual and reproductive health among adolescents. Methods: A descriptive cross-sectional study was conducted in Kathmandu valley to assess the knowledge regarding sexual and reproductive health among adolescents. Total of 200 respondents were selected through non-probability purposive sampling technique. Self-administered written questionnaire was used for data collection. The collected data were analyzed by using descriptive statistics such as frequency, percentage, mean, standard deviation and inferential statistics such as Chi-square test. Results: The findings revealed that most of the respondents had knowledge regarding transmission and protection of HIV/AIDS and STIs but still some respondents had misconception regarding it. The statistical analysis revealed that the total mean knowledge score with standard deviation was 45.02±8.674. Nearly half of the respondents (49.5%) had moderate level of knowledge, followed by inadequate level of knowledge 29.5% and adequate level of knowledge 21.0% regarding sexual and reproductive health. There was statistically significant association of level of knowledge with area of residence (p-value 0.002). Conclusion: Nearly half of the respondents possess some knowledge about sexual and reproductive health but still effective educational intervention is required to increase their knowledge.